Museum Diplomacy and Postcolonial Memory: The Revolusi! Exhibition in Indonesian-Dutch Relations - Riyanto, Budi; Dortant, Willemijn Mechteld Maria; Christianauli, Claudia; Larasaty, Past Novel (Universitas Muhammadiyah Yogyakarta, 2025)
This article analyzes the Revolusi! Indonesia Independent exhibition (2022) at the Rijksmuseum in Amsterdam as a case study of memory diplomacy, demonstrating how museums function as non-state actors in international relations. The exhibition, which aimed to foster reconciliation between the Netherlands and Indonesia, became the center of controversy over the curatorial treatment of the term Bersiap. The study employed a tripartite framework to examine this case, integrating museum diplomacy, memory politics, and postcolonial International Relations (IR) theory. The first lens highlights museums as cultural actors projecting national identity and contributing to soft power while navigating asymmetrical power relations. The second lens situates the exhibition as an arena of norm contestation, where hegemonic Dutch-Indo victimhood narratives clashed with Indonesian decolonial counter-memories. The third lens interprets the controversy through postcolonial diplomacy, revealing how unresolved colonial legacies complicate bilateral reconciliation. Drawing on qualitative methods, the article argues that the Rijksmuseum became a contested diplomatic arena rather than a neutral space of cultural dialogue. The findings underscore that museums have been deeply embedded in power struggles over identity, soft power, and historical memory, making them critical sites for understanding the intersections of heritage, trauma, and diplomacy in postcolonial international relations.